Discovery of the first pincer wasp (Hymenoptera, Dryinidae) from Rovno amber - Perkovsky, Evgeny E.; Olmi, Massimo (Zootaxa, 2018)
Dryinidae (Hymenoptera: Chrysidoidea) are recorded for the first time from Rovno amber (Ukraine), following the discovery of one female of Dryinus janzeni Olmi. Holotypes of D. balticus (Olmi) and D. bruesi (Olmi) previously assigned to the Baltic amber, were actually collected on the coast of Denmark, so that they have to be recorded as specimens in Scandinavian (Danish) amber. As a result, true records of Dryinus species of group 3 (Olmi 1993) in Baltic amber are three: D. janzeni, D. bruesi, because of a second specimen found in true Baltic amber, and D. velteni Olmi. Dryinidae are the 33th hymenopteran family known from Rovno amber. Three species, D. janzeni, D. bruesi and D. balticus are known from understudied Rovno and Scandinavian amber originated from the warmer south coast of the Subparathetys. Dryinus janzeni is the 115th hymenopteran species known from Rovno amber and the first Dryinus record from Ukraine.